THE CONTRIBUTION OF PROFESSIONAL COACH FOR EMOTIONAL AND PSYCHOLOGICAL ADJUSTMENT OF SOCCER PLAYER - José Eduardo Correia Quadros da Silva; Luís Sérgio Gonçalves Vieira; Alexandra Isabel Cabral da Silva Gomes (Journal of Physical Education)
ABSTRACT: The aim of this study was to explore the perception of professional soccer coaches about their contribution to the psychological and emotional player's adjustment. It is a qualitative study and dates were obtained by semi-structured interviews conducted with ten professional soccer coaches. A descendent hierarchical corpus identified four classes organized into two themes. Theme 1 (the coach and soccer player toward competition demands) corresponds to class 1 (soccer coach profile) and 2 (soccer player in competition), and theme 2 (the coach and player psychological dimension), class 3 (player psychological dimension) and 4 (relationship coach-player).Results allowed us to understand that coaches appreciate the player psychological dimension, but they reveal a fragile domain on regular mastery of strategies for player's psychological and emotional regulation.